Enhancing the Capacity of Providers in Mental Health Integration (ECaP-MHI) in Rural Uganda: The Adaptation Process - Wakida, Edith K; Obua, Celestino; Haberer, Jessica E; Bartels, Stephen J (Journal of Multidisciplinary Healthcare, 2023)
Purpose: Uganda adopted the World Health Organization (WHO) model of creating district health management teams (DHMT) comprised of public health officials and administrators to supervise health service delivery at the community level. The purpose of this study was to characterize the perspectives of the DMHT in providing support supervision to primary health-care providers implementing mental health integration using the pre-recorded material. Our aim was to identify barriers to individual uptake and contextual fit, and to solicit solutions for co-designed improvements. Methods: We conducted a qualitative exploratory study using one-on-one interviews informed by the Practical Robust Implementation and Sustainability Model. Results: Members of the DHMT identified a systemic gap in supporting mental health integration into primary care, and reported limited knowledge in how to supervise mental health integration and lacked data on mental health delivery and outcomes. They recommended training of the DHMT in supervising mental health integration supported by standard outcome reports, pre-recorded instructional material by psychiatrists, checklists to help guide and standardize the process, and use of visual aids illustrating mental disorders and treatments for low-health literacy populations. Conclusion: Implementing integrated mental health care using the WHO model of DHMTs as external facilitators and supervisors of primary health-care providers is potentially feasible and scalable, provided that substantial reforms occur such as training in how to provide supervision, standard collection of outcome reports, and practical tools to help guide and facilitate the process
Keywords: District health management team; Practical Robust Implementation and Sustainability Model; Integration of mental health services; Primary healthcare